Answer:
⇒ answer 1
Explanation:
* Lets explain how to find the inverse of a function
- To find the inverse of a function :
# Write y = f(x)
# Switch the x and y
# Solve to find the new y
# The new y is
![f^(-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wdbxkz41ser47cw9774n9ajntnx3zg4rya.png)
* Lets solve the problem
∵ f(x) = 2x + 1
- Put y = f(x)
∴ y = 2x + 1
- Switch x and y
∴ x = 2y + 1
- Solve to find the new y
∵ x = 2y + 1
- Subtract 1 from both sides
∴ x - 1 = 2y
- Divide both sides by 2
∴ (x - 1)/2 = y
- Divide each term in the left hand side by 2
∴ y = 1/2 x - 1/2
- Replace y by
![f^(-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wdbxkz41ser47cw9774n9ajntnx3zg4rya.png)
∴
![f^(-1)(x)=(1)/(2)x-(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vbwt04jf14pzfgfuc4vvbpycfc8x26h44f.png)
* The inverse of the function is
![f^(-1)(x)=(1)/(2)x-(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vbwt04jf14pzfgfuc4vvbpycfc8x26h44f.png)